2015
DOI: 10.1364/ol.40.003276
|View full text |Cite
|
Sign up to set email alerts
|

20-Gbps optical LiFi transport system

Abstract: A 20-Gbps optical light-based WiFi (LiFi) transport system employing vertical-cavity surface-emitting laser (VCSEL) and external light injection technique with 16-quadrature amplitude modulation (QAM)-orthogonal frequency-division multiplexing (OFDM) modulating signal is proposed. Good bit error rate (BER) performance and clear constellation map are achieved in our proposed optical LiFi transport systems. An optical LiFi transport system, delivering 16-QAM-OFDM signal over a 6-m free-space link, with a data ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…[2] on an external cavity injection locking scheme. In the visible region, very few recent reports on external injection locked blue [3] and red [4] semiconductor lasers are available, exhibiting improvement in the locked mode optical power and the modulation bandwidth, however, no report on the employment of SIL is available, to our knowledge, which is highly attractive because of its cost-effective and energy efficient deployment. In this work, we present the performance characteristics of self-injection locked InGaN/GaN blue edge emitting laser by demonstrating a significant enhancement of modulation bandwidth and side-mode-suppression-ratio (SMSR), and reduction in optical linewidth, under self optical feedback scheme, and at three external cavities.…”
Section: Introductionmentioning
confidence: 99%
“…[2] on an external cavity injection locking scheme. In the visible region, very few recent reports on external injection locked blue [3] and red [4] semiconductor lasers are available, exhibiting improvement in the locked mode optical power and the modulation bandwidth, however, no report on the employment of SIL is available, to our knowledge, which is highly attractive because of its cost-effective and energy efficient deployment. In this work, we present the performance characteristics of self-injection locked InGaN/GaN blue edge emitting laser by demonstrating a significant enhancement of modulation bandwidth and side-mode-suppression-ratio (SMSR), and reduction in optical linewidth, under self optical feedback scheme, and at three external cavities.…”
Section: Introductionmentioning
confidence: 99%
“…The threshold current (Ith) of the LD is measured to be 34 mA and found to reduces to 33.7 mA under self-optical feedback mode. This is attributed to the enhancement of the photon density in the active region of the LD after the optical feedback, which has been observed in the literature [1], [2] and considered as one of the signatures of injection locking. The transmitted beam is collimated by an anti-reflection coated aspheric lens (Lens 1, Thorlabs A375TM-B) of focal length 7.5 mm with a reflectance of 0.25-0.5, and passed through a 92:8% pellicle beam splitter (BS, Thorlabs BP108) to enable simultaneous self-optical feedback and performance characterization.…”
Section: Introductionmentioning
confidence: 77%
“…Although injection locking has been comprehensively studied and the underlying physics is well understood in the NIR LDs, they are living in their infancy in the visible region with a handful of reports in the literature. For instance, Lu et al [2] demonstrated ~2.4 times improvement in modulation bandwidth using EIL scheme on 680 nm red vertical cavity surface emitting laser (VCSEL) and successfully transmitted 20 Gb/s 16-quadrature amplitude modulated (16-QAM) orthogonal frequency division multiplexed (OFDM) signal via direct modulation [2]. The work was further extended to include two stage EIL to demonstrate 56 Gb/s LiFi transmission using pulse amplitude modulation (PAM-4) scheme [3].…”
Section: Introductionmentioning
confidence: 99%
“…The reference signal for jamming separation is transmitted through a free space optical (FSO) communication channel. Since the bandwidth of a FSO channel is up to 20 GHz [32,33] a single FSO is able to carry reference signals for canceling jamming signals that covers all the possible RF communication bands The FSO channel carries both of the signal of interest and the jamming signal, and by using the protocols and network model discussed in Section 3, the receiver is able to cancel the jamming signal with the FSO reference signal. Since the optical carriers have much higher frequencies than the radio frequency carriers, the bandwidths of the optical carriers are much larger than the radio frequency counterpart.…”
Section: Introductionmentioning
confidence: 99%